Multidisciplinary Team Care in the Surgical Management of Pituitary Adenoma - Grayson, Jessica W.; Nayak, Agnish; Winder, Mark; Jonker, Benjamin; Alvarado, Raquel; Barham, Henry; McCormack, Ann; Harvey, Richard J. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective Despite multidisciplinary care being commonly recommended, there remains limited evidence supporting its benefits in pituitary disease management. This study aimed to assess the impact of multidisciplinary care in pituitary surgery.Methods A retrospective cohort study was performed comparing pituitary surgery outcomes among consecutive patients within a quaternary referral center in 5 years before and after introduction of a multidisciplinary team (MDT). Primary outcomes were endocrine (transient diabetes insipidus [DI], syndrome of inappropriate antidiuretic hormone [SIADH], and new hypopituitarism) and surgical (cerebrospinal fluid [CSF] leak, epistaxis, intracranial hemorrhage, and meningitis) complications, length of hospital stay, and intrasellar residual tumor.Results 279 patients (89 pre-MDT vs. 190 post-MDT) were assessed (age 54 ± 17 years, 48% female). Nonfunctioning adenomas were most common (54%). In the post-MDT era, more clinically functioning tumors (42 vs. 28%, p = 0.03) were treated. Transient DI and SIADH occurred less often post-MDT (20 vs. 36%, p < 0.01 and 18 vs. 39%, p < 0.01), as well as new hypothyroidism (5 vs. 15, p < 0.01). Hospital stay was shorter post-MDT (5[3] vs. 7[5] days, p < 0.001) and intrasellar residuals were less common (8 vs. 35%, p < 0.001). Complications were more frequent pre-MDT independent of tumor size, hormone status, and surgical technique (odds ratio [OR] = 2.14 [1.05–4.32], p = 0.04).Conclusion Outcomes of pituitary surgery improved after the introduction of an MDT. Pituitary MDTs may benefit both patients and the health system by improving quality of care and reducing hospital stays.
Keywords: multidisciplinary care; pituitary surgery; syndrome of inappropriate antidiuretic hormone; diabetes insipidus; length of stay